2021
DOI: 10.31261/tapsla.9986
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Attention and Extraneous Load

Abstract: There has been a call in recent years for an integration of cognitive load theory into instructed second language acquisition practices to assist language learners by taking advantage of theories on human cognitive architecture. This paper seeks to move the conversation on how this integration might be achieved by presenting findings from survey data conducted with learners enrolled online courses at a cyber-university in South Korea (n = 68). Findings show a statistically significant positive relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Hughes et al ( 2021 ) indicated a significant positive correlation between distraction and ECL. The attention allocated to the main content was reduced by some unrelated cognitive effort.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Hughes et al ( 2021 ) indicated a significant positive correlation between distraction and ECL. The attention allocated to the main content was reduced by some unrelated cognitive effort.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For example, Chang et al (2017) provided evidence that flow experience negatively correlates with ECL (Chang et al, 2017). Hughes et al (2021) indicated a significant positive correlation between distraction and ECL. The attention allocated to the main content was reduced by some unrelated cognitive effort.…”
Section: The Negative Impact Of Ecl On Enjoyment and Attentionmentioning
confidence: 99%
See 1 more Smart Citation